2007
DOI: 10.1186/1741-7015-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance in the MRCP(UK) Examination 2003–4: analysis of pass rates of UK graduates in relation to self-declared ethnicity and gender

Abstract: Background: Male students and students from ethnic minorities have been reported to underperform in undergraduate medical examinations. We examined the effects of ethnicity and gender on pass rates in UK medical graduates sitting the Membership of the Royal Colleges of Physicians in the United Kingdom [MRCP(UK)] Examination in 2003-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
3
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 21 publications
8
83
3
4
Order By: Relevance
“…[2][3][4][5][6][7][8] Similar findings have been reported in the United States 9 and Australia. 10 Some evidence suggests that the ethnic gap might be greatest in assessments of clinical knowledge and skills, but it is also present in machine marked tests of basic medical knowledge.…”
Section: Notessupporting
confidence: 84%
“…[2][3][4][5][6][7][8] Similar findings have been reported in the United States 9 and Australia. 10 Some evidence suggests that the ethnic gap might be greatest in assessments of clinical knowledge and skills, but it is also present in machine marked tests of basic medical knowledge.…”
Section: Notessupporting
confidence: 84%
“…3 It is poorly researched: there are only two substantial studies of the potential bias of examiners by sex, ethnic group, or source of primary medical degree, and these concern the examinations of the MRCP(UK) examination where two examiners work together in pairs. 4,5 Differential candidate performance Dewhurst et al 4 found sex and ethnicity differences among UK graduates (UKGs) in the intercollegiate MRCP Part 2 Clinical Examination (PACES) in [2003][2004] (male candidates failing at 1.5 times the rate of female candidates, and black and minority ethnic (BME) candidates failing at 1.7 times the rate of the white candidates); the latest (2012) published statistics 6 show sex differences (UKG male candidates failing at 1.3 times the rate of UKG female candidates), ethnicity differences (BME UKG candidates failing at 1.3 times the rate of white UKG candidates), and differences with regard to source of primary medical degree (IMGs failing at 3.1 times the rate of UKGs).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the MRCP(UK) Dewhurst et al 4 reported no association between candidate and examiner sex and a small but highly significant interaction of candidate and examiner ethnicity on stations assessing communication skills and ethics. McManus and colleagues detected 'possible sex bias in no examiners and possible ethnic bias in only one' in the MRCP(UK).…”
mentioning
confidence: 99%
“…Several authors have previously attempted to identify students at risk of failing undergraduate or postgraduate exams, but no method has been shown to be completely reliable (McManus et al 2003;Bessant et al 2006;Dewhurst et al 2007;Bowhay & Watmough 2009,). White et al (2009) showed that students who fail an exam can improve their success at the next attempt with a combination of review, reflection and self-assessment.…”
Section: Discussionmentioning
confidence: 99%